Effect of CPAP on cardiovascular events in minimally symptomatic OSA: long-term follow-up of the MOSAIC randomised controlled trial. Issue 1 (14th September 2020) - Tang, Ivan; Turnbull, Chris D; Sen, Dushendree; Craig, Sonya; Kohler, Malcolm; Stradling, John R
Abstract : The effect of continuous positive airway pressure (CPAP) on cardiovascular events is uncertain in minimally symptomatic obstructive sleep apnoea. Previous 2-year follow-up data from the Multicentre Obstructive Sleep Apnoea Intervention Cardiovascular (MOSAIC) trial showed a marginal reduction in cardiovascular events with CPAP therapy. We now present long-term MOSAIC study follow-up data. Median (first quartile, third quartile) follow-up was 5.0 (2.2, 5.0) and 3.7 (1.5, 5.0) years for CPAP and standard care, respectively. Compared to standard care, CPAP had no statistically significant effect on the risk of cardiovascular events (HR=0.83, p=0.54, 95% CI 0.46–1.51).